Brave New Wealthy World: Winning the Struggle for World Prosperity - Edmunds, John (Pearson, 2003)
Brave New Wealthy World demonstrates how today's international financial arrangements arespreading prosperity and well-being more widely than ever before-and what it'll take to spreadthe wealth to virtually every corner of the Earth. John C. Edmunds proposes a new symbiotic relationship between rich and poor countries thatoffers powerful benefits to both. He demonstrates why "first world" investors will increasinglydepend upon growth in emerging economies to achieve the returns they need and offers a blueprintfor transforming emerging nations' financial systems into powerful drivers of economic growth. This book cuts through the conventional wisdom and ideologies that hide the true implicationsof globalization-and reveals a pragmatic path to a hopeful future. The long-term forecast: prosperity spreading worldwide The middle class grows- by billions Financial assets: the new catalysts of world prosperity Securitization: unleashing the power of emerging economies Why "rich" countries will increasingly depend on investments in emerging economies A new symbiosis between rich and poor Proven policies for promoting the investments that supercharge growth Overcoming the obstacles to investment in emerging economies Powerful lessons from three recent boom/bust cycles A tale of three booms Population trends and their surprising implications Demographics and economic destiny Accelerating the economic revolution that's bringing new prosperity to billions "Professor Edmunds does an outstanding job in explaining-in great detail and with examplesdrawn from concrete experience-why liquidity matters and why financial services make all thedifference if wealth is to be created. Extremely useful insight into the process of adding valuethrough securitization." -Hernando de Soto, author of The Mystery of Capital and President of the Institute for Liberty and Democracy (ILD) "I learned more about economics talking to Edmunds than I ever did in graduate school. Heshows that capitalism works. It can even work in developing countries. Capitalism is alreadyequalizing the distribution of income and bringing prosperity to many third world places.Capitalism can and will work if governments do not get in its way." -Peter T. Paul, Chairman, Sequoia National Bank, California "A provocative book with rich insights gleaned from the author's extensive professionalexperiences in developing countries." -James E. Austin Snider Professor of Business Administration, Harvard Business...